2020
DOI: 10.1590/s2175-97902019000318302
|View full text |Cite
|
Sign up to set email alerts
|

Laurus nobilis L.: assessment of the cytotoxic and genotoxic potential of aqueous extracts by micronucleus and Allium cepa assays

Abstract: Laurus nobilis L. is a large shrub belonging to the Lauracea family. Its leaves are widely used for food seasoning as well as in folk medicine. Various studies have demonstrated the antiproliferative, antifungal and antibacterial effects of Laurus nobilis, but no studies have investigated the genotoxic effect of the aqueous extract of the plant. The objective of this study was to analyze the genotoxic potential of an aqueous extract of leaves, using the Allium cepa assay and mouse peripheral blood cell micronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The results found in this work suggest that the excessive cytotoxic damage caused on the study population could be inducing apoptosis 19 , so that the amount of altered cells is reduced, resulting to the lack of significance for the data of this work.…”
Section: Resultsmentioning
confidence: 79%
“…The results found in this work suggest that the excessive cytotoxic damage caused on the study population could be inducing apoptosis 19 , so that the amount of altered cells is reduced, resulting to the lack of significance for the data of this work.…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have revealed the attendance of these biomolecules in these extraction forms. Silva et al analyzed the aqueous extract of L. nobilis and showed the presence of flavonoid and phenolic molecules (29). Pugazhenti et al identified the composition of Indian laurel and found that both ethanolic and aqueous extracts contained flavonoid and phenolic compounds (30).…”
Section: Discussionmentioning
confidence: 99%
“…Anticonvulsant activity, aflatoxigenic, insecticides and repellent activity of the leaf essential oil was reported in previous works (Sayyah et al, 2002;Erler et al, 2006;Atanda et al, 2007). Antioxidant activity of L. nobilis essential oil was also being studied (Baratta et al, 1998) Therefore, considering the importance of toxicogenetic investigation of plant the possible effects on Central Nervous System of laurel essential oil (Caputo et al, 2017) and cytotoxic and genotoxic potential of the aqueous extract of L. nobilis leaves was recently prouved (Silva et al, 2020). Tunisian L. nobilis floral buds' oil was evaluated for their antioxidant activity by two methods: β-carotene bleaching (BCB) test and 2.2-diphenyl-β-picrylhydrazyl (DPPH) assay (Bouzouita et al, 2009).…”
Section: Academicpresmentioning
confidence: 99%